After Alicia spent 1/3 of her money, she has 2/3 of her money remaining.
Let's say Alicia had x dollars.
After spending 1/3 of her money, Alicia has 2/3*x = 2x/3 dollars remaining.
After Neha spent $10, she has (x-$10) dollars left.
According to the second part of the problem, 2x/3 = 1/2(x-$10).
Multiplying both sides of the equation by 2, we get 4x/3 = x-$10.
Multiplying both sides by 3/4, we get x = 3/4(x-$10)
Expanding the equation, we get x = 3/4*x - 3/4*10
Simplifying the equation, we get x = 3/4*x - 30/4
Combining like terms, we get x - 3/4*x = 30/4
Simplifying the equation, we get 1/4*x = 30/4
Multiplying both sides of the equation by 4, we get x = 30
The total amount the two had was $66, which means Alicia had $66 - $10 = $<<66-10=56>>56 left after spending $10.
Since Alicia had 2/3 of her money remaining, she had 2/3*$56 = $<<2/3*56=37.33>>37.33 left
The amount of money Neha had left was 1/2 * $37.33 = $<<1/2*37.33=18.66>>18.66. Answer: \boxed{18.66}.
Alicia and Neha had a total of $66. After Alicia spent 1 3 of her money and Neha spent $10, the amount of money Alicia had left was 1 2 of the amount of money Neha
1 answer